PENGGUNAAN AYAT-AYAT AL-QUR’AN DALAM TRADISI SALAT ROBO’-ROBO’ DI DESA SELAT REMIS, TELUK PAKEDAI, KUBU RAYA, KALIMANTAN BARAT: ANALISIS SOSIOLOGI PENGETAHUAN - Ihsan Nurmansyah; Luqmanul Hakim Haris (Sekolah Tinggi Agama Islam Sadra, 2022)
This paper discusses the use of verses of the Qur'an in the Robo'-Robo' prayer tradition in Selat Remis Village, Teluk Pakedai District, Kubu Raya Regency, West Kalimantan. This tradition uses verses of the Qur'an by reading selected surahs in its implementation which is carried out once a year, namely on the last Wednesday of the month of Safar. Therefore, to find out the meaning of the use of the verses of the Qur'an in the Robo'-Robo' prayer tradition is to use the sociological theory of knowledge introduced by Karl Mannheim. The source of the data was obtained from observations and in-depth interviews at the research site. The results of this study are: 1) the objective meaning in the perspective of the Pakedai Bay community, namely preserving tradition as a form of obedience to a cleric named Guru Haji Ismail Mundu by finding manuscripts or hand notes that are used as references in that tradition. 2) expressive meaning in the view of the Pakedai Bay community, namely as a means of repelling reinforcements, avoiding disease, gaining safety, wanting a harmonious household, and after carrying out the tradition feel peace, comfort and tranquility. 3) the documentary meaning of the Robo'-Robo' prayer tradition is the formation of a habit as a forum for togetherness and intimacy for the Pakedai Bay community.